The pace of convergence of population aging in Latin America: opportunities and challenges - Brenes Camacho, Gilbert (2009)
Some of the fastest demographic transitions in the world have been observed in Latin American countries. Fertility and mortality declining have occurred in less than half the time observed in industrialized countries. Population aging is also occurring rapidly in the region. However, its socioeconomic consequences take longer to happen. Socioeconomic disadvantages experienced by current cohorts of Latin American elderly are more resistant to change over time because of the persistence of cohort effects. The slower pace of population aging with respect to other demographic dynamics translates into both opportunities and challenges. This paper intends to describe the differences in the population aging process across Latin American countries, and how these differences can show the path for institutional changes that can improve the welfare of Latin American nations. The paper will first explore how advanced different Latin American countries are in their population aging process. The paper will link this information with data about Social Security coverage among the labor force, labor force formalization and availability of caretakers. Countries that are demographic transition leaders have had higher proportions of educated people, as well as proactive governments that created welfare institutions that still benefit the population in most need. On the contrary, most of the countries that are still going through the transition have been characterized by income and wealth inequality and an absence of political disposition to advance human development policies. The countries that are still far away in their aging process will be able to avail from their demographic situation consensus to develop policies and institutions that improve the human development of their populations can be reached. The article concludes highlighting the need for reforms in terms of Social Security coverage, not only pension reform, for securing the well-being of Latin American elderly in the near future.